HEPATOPANCREAS PARTICIPATION IN THE BODY LENGTH AND WEIGHT OF THE STOMATOPOD ORATOSQUILLA NEPA - SREEJA, J.; GEETHA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
The present study consider the hepatopancreas participation in the body length and weight of the stomatopod, Oratosquilla nepa.